ANALISIS BREAK EVEN POINT SEBAGAI PERENCANAAN LABA PADA UMKM AYCA OPAK GAMBIR DI KECAMATAN KANIGORO BLITAR - Nofitasari, Dian; Pravitasari, Dyah (ITB AAS Indonesia Surakarta, 2024)
MSME businesses have a major contribution to the economy of Indonesian society, because this type of business has a role in providing employment opportunities. Every entrepreneur definitely wants his business to run well and produce maximum profits, just like MSME Ayca Opak Gambir. However, the owner's profit planning is still limited to estimates with the assumption that the more products sold, the more profits he will receive.The aim of the research is to carry out calculations break even point so that find out the break even point and margin of safety to know percentage reducing sales to safe limits and trying to plan the desired profit, but before that, first separate costs which have not been done before. The method used is a descriptive quantitative method. The data sources used are primary data in the form of interviews with business owners and documentation in the form of financial reports. The results of this research are break even point will be achieved at a sales volume of IDR 286,139,344 or 5,752 units. for safe limits o rmargin of safety is 32% or IDR 133,860,656. If you want a profit increase of 110%, the owner can make sales of IDR 429,222,295 or a total of 8,628 units. Keywords : Break Even Point, Margin Of Safety, Profit Planning